Impacts of Land Use and Land Cover Change on Vegetation Diversity of Tropical Highland in Ethiopia - Abdulbasit Hussein (Applied and Environmental Soil Science)
Ethiopia has undergone a substantial shift in land use and land cover (LULC), which is home to the majority of the human and animal population. Land degradation has occurred in the Ethiopian highlands as a result of modifications in LULC caused by poor farming methods, high livestock population, and human pressures. Most researchers identified the many LULC drivers and their impact on floristic composition. All of these manifestations have the potential to have major consequences for land users and individuals whose livelihoods rely on the products of a healthy environment. This change in LULC type, combined with poor land management practices in Ethiopia, puts land in jeopardy of erosion, resulting in accelerated soil degradation. All LULC variables, such as the spread of various agricultural activities, the production of fuelwood and charcoal, cutting trees for construction resources, settlements, and revenue growth, are associated with population increase and resettlement. In Ethiopia, the lack of a relevant forest policy implementation on the ground is recognized as a cause pushing deforestation and other landscape changes. This review paper aimed to compile the effects of land use land cover changes on Ethiopian vegetation.